Evaluation of Decentralisation Policy: Impact on Regional Development - Malik, Saharuddin; Aisyah (Cendekiawan Indonesia Timur, 2024)
This study evaluates the impact of decentralisation policies on regional development, focusing on the redistribution of administrative powers from central to local governments. Decentralisation is often implemented with the aim of improving governance, promoting local autonomy, and enhancing public service delivery. This research explores how these policies have influenced economic growth, infrastructure development, and social welfare at the regional level. Using a mixed-methods approach, including quantitative analysis of regional development indicators and qualitative case studies, the findings reveal a complex relationship between decentralisation and regional outcomes. While some regions have experienced significant improvements in governance efficiency and socio-economic conditions, others continue to face challenges such as uneven resource distribution and capacity constraints. The study concludes with policy recommendations aimed at optimizing decentralisation frameworks to ensure balanced and sustainable regional development.